Effect of Sub Toxic Dose of Ephedra Altissima Methanolic Extract on Reproductive System of Male Albino Mice - Mezogi J1, Abusaida H2, El Jaafari H3, Shibani N4, Dali A5, Abuelkhair K1, Shalabi S2, Aburawi S6* (AlQalam Journal of Medical and Applied Sciences, 2020)
Background and objectives: Ephedra is nonflowering plants belonging to Ephedraceae family. There is little information available concerning toxicity. The aim of this work is to carry out phytochemical screening, sperm parameters, and histological study. Materials and Methods: Fresh aerial parts of Ephedra collected, identified, then air-dried. Phytochemical screening of methanolic extract of Ephedra powder using standard procedures were carried out. Twelve male albino mice (25-30 g), were divided into two groups. Mice were treated (i.p.) for 14 days with 1% T80 (5mL/kg), and extract (3000mg/kg) as treated group. At the end of experiment, mice were killed by cervical dislocation, dissected and testis, cauda epididymis and vasa deferentia collected. Seminal fluid collected for sperm count, motility and morphology. Testis were kept in formalin for histological examination. Results: Phytochemical screening showed the presence of carbohydrates, phenols, sterols, saponins, tannins, terpenoids, flavonoids and alkaloids in Ephedra Altissima stem extracts. Ephedra extract caused decrease in sperm count; but it did not show any change in sperms motility compared to the control mice. There is increase in the number of abnormal sperms morphology in mice treated with extract; the sperms tail treated group were much affected than the head. Histological examination showed no structural alteration in the seminiferous epithelium of the treated mice testis compared to control mice. Conclusions: It is concluded that methanolic extract of Ephedra altissima stems have the potential to affect male mice reproductive functions but not affect the structure at the given high dose and short period of treatment.